STRATEGI PENINGKATAN KETERAMPILAN CALON GURU DALAM MENERAPKAN PEMBELAJARAN AKTIF MELALUI MEI (MODELLING, ENGAGING, AND INTEGRATING) (Strategy in Improving Prospective TeachersÃ¢â¬â¢ Skills in Implementing Active Learning through MEI (Modelling, Engaging, an - Fadlan, Andi (KREATIF, 2010)
The dissatisfactory quality of education in Indonesia showed that the quality of teaching and learning process done by teachers & students was still low. Learning paradigm still focused on a teacher only (teacher centered learning) that caused learning process unattractive and monotonous, and it did not give a challenge for students. As a result, the graduates, both of primary and secondary education levels, became static humans who had no creativity and innovation in their life. There were some factors that made difficult to change teacher paradigm in teaching and learning activity, namely teacherÃ¢â¬â¢s low commitment and skill in implementing active teaching-learning process. Therefore, teachers training institution (LPTK) should prepare the students to have skills in implementing active teaching and learning. One of some efforts that could be done to improve studentsÃ¢â¬â¢ skill, as prospective teachers, in implementing an active learning was that by implementing MEI strategy. It covered: (1) Modelling (a lecturer as a model in implementing active learning in the class), (2) Engaging (it involves students in active learning. in this case, planning, processing and evaluating of the teaching-learning activity done by a lecturer reflected the real implementation of active learning), and (3) Integrating (it integrates active learning in all subjects theoretically and practically, like the subjects of teaching and learning strategy, learning design, development of learning media, learning assessment, and microteaching). Keyword: prospective teacherÃ¢â¬â¢s skills, active learning, and MEI